Association of low serum magnesium with diabetes and hypertension: Findings from Qatar Biobank study. (December 2019) - Shi, Zumin; Abou-Samra, Abdul Badi
Abstract: Aim: We aimed to examine the association between serum magnesium and diabetes and hypertension among Qatari adults. Methods: In the cross-sectional study, we used data from 9693 Qatari participants aged 20 years and above attending the Qatar Biobank (QBB) Study. Blood samples were analyzed in a central lab. Habitual food consumption was assessed by a food frequency questionnaire. Reduced rank regression was used to construct magnesium related dietary pattern (MRDP) using serum magnesium as a response variable. Diabetes was defined by blood glucose, HbA1c or known diabetes. Prediabetes was defined as HbA1c between 5.7% and 6.4%. Subclinical magnesium deficiency was defined as serum magnesium <0.85 mmol/L. Results: The prevalence of diabetes, prediabetes and subclinical magnesium deficiency was 18.9%, 11.5% and 59.5%, respectively. Across the quartiles of serum magnesium from high to low, the prevalence ratios (PR 95%CI) for diabetes were 1.00, 1.35, 1.88, and 2.70 (95%CI 2.38–3.05), respectively (p for trend <0.001). The presence of hypertension significantly increased the probability of diabetes along a wide range of low serum magnesium. A low intake of MRDP was also positively associated with diabetes and high HbA1c. Conclusion: Subclinical magnesium deficiency is common in Qatar and associates with diabetes, prediabetes and hypertension in Qatari adults.